Facile synthesis of F-doped g-C3N4/Bi2Fe4O9 heterostructure with Z-scheme for enhanced photocatalytic performance in NO oxidation. (November 2020) - Liu, Huazhong; Wang, Xiaolan; Xu, Han; Luo, Chunxia
Abstract: Graphitic carbon nitride (g-C3 N4 ) with fluorine (F) doping was synthesized by a hydrothermal technique, and F-doped g-C3 N4 /Bi2 Fe4 O9 composites were synthesized by electrostatic self-assembly technique. The crystal structures were studied by X-ray diffraction, the morphology was determined by transmission electron microscope images, and the F doping was verified by energy dispersive X-ray analysis, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The N2 adsorption/desorption results showed that introducing Bi2 Fe4 O9 nanoparticles into F-doped g-C3 N4 reduced the specific surface area and volume of the pores. This could be attributed to the Bi2 Fe4 O9 nanoparticles partially blocking the pores of F-doped g-C3 N4 . The photocatalytic performance of F-doped g-C3 N4 /Bi2 Fe4 O9 composites was studied by oxidizing NO under visible irradiation. The photocatalytic performance indicated that the presence of Bi2 Fe4 O9 increased the photocatalytic activity of F-doped g-C3 N4 by up to 100%. The increased photocatalytic performance could be ascribed to a decreased combination rate of the charge carriers. Moreover, scavenger testing study showed that the reactive species, including h +, O2, and ·O2 −, played important roles in the photocatalytic reactions. Highlights: F-doped g-C3 N4 /Bi2 Fe4 O9 composite was synthesized by electrostatic self-assembly. With 6 wt% of Bi2 Fe4 O9, F-doped g-C3 N4 /Bi2 Fe4 O9 had the maximum reaction activity. The increased photocatalytic performance was explained by a Z-scheme mechanism.